Analysing The Relationship Between Worker Knowledge And Practices On Performance With Organisational Commitment As Mediator In Chinese Industry - Hui , Luo; Abbas Ali, Dhakir (Cuestiones de Fisioterapia, 2023)
Using organisational commitment as a mediator, this study explored the connection among employee knowledge and worker performance in a chinese sector. To which extent does organisational commitment improve the connection between worker expertise (collected from education, instruction, and experiences) and their performance outcomes, that was this research's primary goal. Employing a quantitative study approach, data was gathered from employees in different chinese manufacturing industries using a well-organised survey. To assess the interrelationships of the variables, statistical methods such as descriptive analysis and regression were applied to 676 eligible submissions. Employee knowledge has been defined as a mixture of knowledge of technology, problem-solving abilities, and flexibility, however organisational commitment was characterised as the psychological investment, devotion, and sense of obligation workers have for the organisations they work for. The results showed that employee knowledge significantly influenced worker performance, showing that well-informed workers could better respond to new technologies, overcome obstacles, and accomplish corporate goals. The results also showed how employee knowledge strongly affected organisational commitment, which could indicate that knowledge growth initiatives succeeded in making employees more committed and dedicated to the company. In addition, organisational commitment served as a bridge, reinforcing the connection between worker knowledge and performance results. It was determined that there was a cooperative impact that boosted personal and corporate performance when worker knowledge was enhanced, and commitment was fostered jointly. Investments in creating knowledge and developing commitment were highlighted as crucial points for chinese industries in the study, which supplied important conclusions.